Effect of regulating airway pressure on intrathoracic pressure and vital organ perfusion pressure during cardiopulmonary resuscitation: a non-randomized interventional cross-over study. Issue 1 (December 2015) - Kwon, Younghoon; Debaty, Guillaume; Puertas, Laura; Metzger, Anja; Rees, Jennifer; McKnite, Scott; Yannopoulos, Demetris; Lurie, Keith
Abstract Background The objective of this investigation was to evaluate changes in intrathoracic pressure (Ppl), airway pressure (Paw) and vital organ perfusion pressures during standard and intrathoracic pressure regulation (IPR)-assisted cardiopulmonary resuscitation (CPR). Methods Multiple CPR interventions were assessed, including newer ones based upon IPR, a therapy that enhances negative intrathoracic pressure after each positive pressure breath. Eight anesthetized pigs underwent 4 min of untreated ventricular fibrillation followed by 2 min each of sequential interventions: (1) conventional standard CPR (STD), (2) automated active compression decompression (ACD) CPR, (3) ACD+ an impedance threshold device (ITD) CPR or (4) ACD+ an intrathoracic pressure regulator (ITPR) CPR, the latter two representing IPR-based CPR therapies. Intrapleural (Ppl), airway (Paw), right atrial, intracranial, and aortic pressures, along with carotid blood flow and end tidal CO2, were measured and compared during each CPR intervention. Results The lowest mean and decompression phase Ppl were observed with IPR-based therapies [Ppl mean (mean ± SE): STD (0.8 ± 1.1 mmHg); ACD (−1.6 ± 1.6); ACD-ITD (−3.7 ± 1.5, p  < 0.05 vs. both STD and ACD); ACD-ITPR (−7.0 ± 1.9, p  < 0.05 vs. both STD and ACD)] [Ppl decompression (mean ± SE): STD (−6.3 ± 2.2); ACD (−13.0 ± 3.8); ACD-ITD −16.9 ± 3.6, p  < 0.05 vs. both STD and ACD); ACD-ITPR −18.7 ± 3.5, p  < 0.05 vs. both STD and ACD)]. Interventions with the lower mean or decompression phase Ppl also demonstrated lower Paw and were associated with higher vital organ perfusion pressures. Conclusions IPR-based CPR methods, specifically ACD-ITPR, yielded the most pronounced reduction in both Ppl and Paw and resulted in the most favorable augmentation of hemodynamics during CPR.